Implementation of an Emitting Led Circuit in a Visible Light Communications Positioning System - Soto-Gomez, J; Navarrete-Cardenas, R (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, two LED emitting circuits are implemented in a VLC positioning system, a regular Bias-Tee and a circuit proposed by Ghassemlooy, aiming to provide the system with portability and functionality. For this, an Arduino Nano is used in the emitting circuit together with an AD9850 signal generator circuit. For the receiver circuit a Thorlabs PDA36-EC photodetector, an XMOS for data acquisition and a Raspberry Pi for data processing are used. Subsequently a brief comparison is made between the two emitting circuits, comparing the power received by the photodetector as a function of the emitter-receiver distance. © 2017 IEEE.